Applying software agent in collaborative software maintenance - Wan Mayu Othman, Wan Noor Rafida; Abdullah, Rusli; Selamat, Mohd Hasan; Shaharin, Shahnita (2007)
Software maintenance is the most expensive process and least predictable stage of the software life cycle. Yet these activities are inevitable to produce useful and successful software which will stimulate user generated request for change and improvement. This become more complex in term of large scale project that needed collaboration of many software engineers that situates in distributed locations. In a collaborative software maintenance environment, direct communication is difficult and most impossible to occur. To coordinate and manage a large community mechanism is required to help them understand the system development progress. This is solved by developing a system that provides a mechanism of collaboration via application sharing and email sending. This mechanism becomes more effective with the integration of software agent technology that is able to support the software maintenance environment which includes Staff Agent, Request Agent and Client agent.